Paving the way ahead: protocol optimization of mouse models in crush syndrome related acute kidney injury research - Qiao, Ou; Wang, Xinyue; Li, Zizheng; Han, Lu; Chen, Xin; Zhang, Li; Bao, Fengjiao; Hao, Herui; Hou, Yingjie; Duan, Xiaohong; Saeed, Sania; Li, Ning; et al. (Frontiers in Pharmacology, 2024)
Backgrounds: Crush syndrome (CS) is the leading cause of death after earthquakes, second only to direct trauma. Acute kidney injury (AKI) is the most severe complication of CS. Research based on the CS-AKI mouse model and kidney function assessment by glomerular filtration rate (GFR) helps to elucidate the pathogenesis of CS-AKI, which contributes to effective treatment measures.Methods: Mice were modeled by the multi-channel small animal crushing platform. We set up different CS-AKI modeling parameters by applying different crushing weights (0.5 kg, 1.0 kg, 1.5 kg), crushing durations (6 h, 12 h, 16 h), and decompression durations (6 h, 12 h, 24 h). The GFR, serum creatinine (SCr), blood urea nitrogen (BUN), kidney tissue Kim-1 mRNA and Ngal mRNA expression levels, and HE staining were examined to evaluate the results of different protocols.The results showed that with the crushing weight increased, the kidney function assessment's gold standard GFR significantly decreased, and the levels of SCr and BUN increased.Meantime, the higher extension of inflammatory cell infiltration in the kidney was found with the longer crushing durations. The degree of kidney injury continued to worsen with the duration of decompression, indicating severe damage after reperfusion, which was associated with tubular injury and a sustained elevation of the inflammatory state.We successfully constructed CS-AKI mouse models with different severities under the above parameters. Applying 1.5 kg for 16 h and then decompressing for 24 h induced severe AKI. These findings provide clues for further exploration of the mechanism and treatment of traumatic AKI.